1982
DOI: 10.1007/bf00282582
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of microangiopathy, plasma glucose and other risk factors in 3583 diabetic patients: A multinational study

Abstract: In a multinational study, fasting plasma glucose values in 3583 diabetic patients, aged 34-56 years, were related to the characteristics of these subjects and to the presence and severity of microangiopathy as ascertained by standardised methods. The patients were from nine different populations and ranged in number from 193 to 686 per population (London, Warsaw, Berlin (FRG), New Delhi, Tokyo, Havana, Oklahoma Indians, Arizona Pima Indians, and a national sample in Switzerland). In the total group, mean fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 8 publications
4
28
1
Order By: Relevance
“…These discrepancies may be due to less than optimal treatment by today's standards, inadequate sample size, inadequate duration of the study, varying starting points in the disease or the possibility that the stage being studied was already irreversible. Duration of diabetes is a very important factor in the development of diabetic nephropathy as demonstrated in several studies; [29][30][31][32][33][34][35][36][37][38][39][40][41] this has also been confirmed in our study -the longer the duration of diabetes, the higher the frequency of diabetic nephropathy. However, duration of the disease is not the only factor since many patients with longstanding diabetes will not develop nephropathy, as shown by the normal group in our study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These discrepancies may be due to less than optimal treatment by today's standards, inadequate sample size, inadequate duration of the study, varying starting points in the disease or the possibility that the stage being studied was already irreversible. Duration of diabetes is a very important factor in the development of diabetic nephropathy as demonstrated in several studies; [29][30][31][32][33][34][35][36][37][38][39][40][41] this has also been confirmed in our study -the longer the duration of diabetes, the higher the frequency of diabetic nephropathy. However, duration of the disease is not the only factor since many patients with longstanding diabetes will not develop nephropathy, as shown by the normal group in our study.…”
Section: Discussionsupporting
confidence: 87%
“…31 -35 We did not find a good correlation between degree of proteinuria and diabetic control. Although some studies, in particular, the large trials of the University group diabetes program (UGDP) 38 which were concluded in the late 1960s, did not show good correlation of hyperglycemia with diabetic nephropathy, other population-based cross-sectional studies 38,39 and the most recently published results of the diabetes complications and control trial (DCCT) 40 support the cause-and-effect relationship between hyperglycemia and diabetic nephropathy. These discrepancies may be due to less than optimal treatment by today's standards, inadequate sample size, inadequate duration of the study, varying starting points in the disease or the possibility that the stage being studied was already irreversible.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective data will investigate this possibility further. Similar logistic analyses for triglyceride and glucose data from five of the 14 populations in this study showed that higher glyceride values in the diabetics were associated with 'Large-Vessel Disease', 'Stroke Only' and 'Leg VD' categories, while fasting glucose showed no association with 'Heart VD' [29]. Withincentre analyses showed blood pressure, followed by age, to be the most consistent independent variables associated with LVD and HVD.…”
Section: Large-vessel Disease Prevalencesupporting
confidence: 65%
“…Thus, one might expect that high ADMA levels in diabetic retinopathy subjects reflect a phenomenon of the coexistence of diabetic retinopathy and diabetic nephropathy (13). The mean creatinine levels were, however, within the normal range in both diabetic groups.…”
Section: Research Design Andmentioning
confidence: 87%